Psyren. 11, The two test subjects - Iwashiro, Toshiaki, 1977- (Shonen Jump manga., 2013)
Kagetora and his team go searching for information about Miroku Amagi at the Spring Breeze Academy, where Kagetora clashes with the Star Commander of W.I.S.E., Junas, and Miroku takes on a psionist so powerful that Miroku wants to recruit him.